Case Report : A Symptomatic Case of Hymenolepis diminuta Infection in an Urban-Dwelling Adult in Malaysia - Arine Fadzlun, Ahmad; Romano, Ngui; Jaxinthe, Ong; Farikha, Sarip; Wan Hafiz, Wan Ismail; Hasidah, Omar; Zurainee, Mohamed Nor; Amirah, Amir; Yvonne A. L., Lim; Rohela, Mahmud (The American Society of Tropical Medicine and Hygiene, 2017)
A case of Hymenolepis diminuta infection in a 43-year-old Malaysian male with persistent abdominal colicky pain is reported. Endoscopy revealed whitish worms in the lumen of the small intestine, which were identified as H. diminuta after microscopy. Patient was successfully treated with a single dose of praziquantel (25 mg/kg).